2009
DOI: 10.1007/s11099-009-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic electron transport at low temperatures in the green algal foliose lichens Lasallia pustulata and Umbilicaria hirsuta affected by manipulated levels of ribitol

Abstract: In lichens, ribitol is known as a carbon storage compound, an osmotic agens involved effectively in cell compartments protection during dehydration of lichen thalli and as a cryoprotective compound. In our study, we investigated the effect of ribitol on photochemical processes of photosynthesis in foliose lichens [Lasallia pustulata (L.) Mérat., Umbilicaria hirsuta (Sw. ex Westr.) Hoffm.] at low temperature. The effects of three concentrations of ribitol, added externally to thalli segments on several chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Thus, ribitol may have positive effect on primary photosynthetic processes in lichens when added in the concentrations ranging between 8 -32 mM. Such conclusion might be supported also by the decrease in NPQ caused by 8 -32 mM ribitol (Hájek et al 2009) while it was Fig. 3.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, ribitol may have positive effect on primary photosynthetic processes in lichens when added in the concentrations ranging between 8 -32 mM. Such conclusion might be supported also by the decrease in NPQ caused by 8 -32 mM ribitol (Hájek et al 2009) while it was Fig. 3.…”
Section: Discussionmentioning
confidence: 81%
“…Fontaniella et al 2000). In our previous study (Hájek et al 2009), we showed that addition of ribitol improved photosynthetic activity of two foliose lichen species (Lasallia pustulata and Umbilicaria hirsuta) at freezing temperature. In recent experiments, we have focused on utilization of ribitol in synthesis of lichen secondary metabolites.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Particular physiological responses to limiting environmental factors, such as resistance to photoinhibition (Balarinová et al 2014), temperature (Colesie et al 2018), freezing tolerance (Hájek et al 2016), and strategies of water uptake, and dehydration resistance (Jonsson Čabrajić et al 2010), were studied as well. Last but not least, several studies have addressed photosynthetic performance evaluated by gas exchange (Kappen et al 1995, Cao et al 2015, chlorophyll (Chl) fluorescence exploiting (1) fast (OJIP) transients (Bednaříková et al 2020a,b), (2) slow Kautsky kinetics with quenching analysis (Hájek et al 2001(Hájek et al , 2009 or (3) monitoring of in situ effective quantum yield of PSII (Cho et al 2020). Some studies combine gas exchange and Chl fluorescence measurements (e.g., ten Veldhuis et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of monosaccharides and polyols in lichen mycobiont is an adaptive feature for dealing with the complete dehydration [20] , [21] . Ribitol level modifies the photosynthetic activity in some green algal foliose lichens [22] .…”
Section: Introductionmentioning
confidence: 99%